Motor skill experience modulates attentional processing regardless of open- or closed-skill types: an ERP study - Aly, Mohamed; Alzahrani, Turki; Fakehy, Mohammed; Abass, Mohamed; Mohamed, Sheref (Frontiers in Psychology, 2024)
BackgroundAttentional engagement, the ability to maintain focus on relevant tasks, plays a crucial role in optimizing human performance. Studies have shown that athletes exhibit superior attentional engagement compared to non-athletes; however, it remains unclear if these benefits persist in non-sport-related tasks or differ across types of sports expertise, such as open-skill versus closed-skill sports.MethodsNinety-three young adults, divided into open-skill athletes (n = 31), closed-skill athletes (n = 31), and a control group (n = 31), completed an auditory oddball task while the P3 component of event-related potentials was measured to assess attentional processing. Aerobic fitness was assessed using the YMCA fitness test, and linear regression models, adjusted for confounders, examined the relationship between aerobic fitness and attentional processing.ResultsFindings revealed that both open- and closed-skill athletes exhibited significantly larger P3 amplitudes than non-athletes, indicating enhanced attentional engagement. However, no significant differences in response time or response accuracy were observed between the groups. Hierarchical regression analysis further demonstrated a positive correlation between aerobic fitness and P3 amplitude, underscoring the role of aerobic fitness in cognitive processing.ConclusionThese findings suggest that participation in either open- or closed-skill sports can enhance attentional engagement beyond the sports context in healthy young adults, with aerobic fitness playing a key role in supporting cognitive performance. Additionally, this study extends previous findings from Western and Asian literature by providing evidence from an Egyptian sample, thereby supporting the generalizability of the cognitive benefits of aerobic fitness and sports participation across different cultural contexts.